Functional foods from Quercus infectoria galls and their bioactivities - Sulaiman, Fatimatul Akmal; Mohamed Iqbal, Mohammad Anwar; Darnis, Deny Susanti; Adam, Farook; Bakhtiar, M. Taher (2018)
Plant has antimicrobial properties as the extract is used in food industry, pharmaceuticals and alternative medicine. The aims of this study were to isolate metabolites from Quercus infectoria galls and to determine the antimicrobial and antioxidant properties of extracts and isolated compounds. The galls were extracted using soxhlet apparatus with n-hexane (HEX), dichloromethane (DCM) and methanol (MeOH), successively. The crude extracts were fractionated and separated using chromatographic techniques on silica gel. The isolated compounds were characterized using spectroscopic techniques. The antimicrobial activities were determined using disc diffusion method. The antioxidant activities were determined DPPH free radical scavenging activity and β-carotene bleaching assay. The cytotoxicity of isolated compounds was tested on MCF-7 using MTT assay. Methyl gallate (QIM 1) and gallic acid (QIM 2) were isolated from MeOH extract. The extracts and isolated compounds showed antimicrobial activities against Staphylococcus aureus, Bacillus cereus, Pseudomonas aeruginosa, Escherichia coli Candida albicans, Candida krusei and Aspergillus niger ATCC16404. In β-carotene bleaching assay, QIM 1 and QIM 2 exhibited 67 % and 66 % antioxidant activity. The present study revealed that isolated compounds showed potential as antioxidant agent and had cytotoxic effect on MCF-7. Meanwhile, the compound QIM 2 had antimicrobial properties and synergistic effect with chloramphenicol.